Co-creation of educational commons spaces to reverse inequalities: project SMOOTH and the Children's Club - Fernandes, Natália; Sarmento, Teresa; Barra, Marlene; Silva, Daniela; Martins, Fernanda; Casanova, Joana R. (Frontiers in Sociology, 2023)
This article presents an action-research project from the EU-funded SMOOTH project, which focuses on the potential of Educational Commons to address educational inequalities. The project adopts an emergent paradigm that views spaces for collaboration, content co-creation, socialization, governance, and play as catalysts for reversing inequalities. The action-research, conducted in a disadvantaged non-formal education setting in northern Portugal, involved children aged 8–10 years old. Over a span of 10 months, the innovative action-research program aimed to achieve several objectives: (1) reversing inequalities faced by vulnerable social groups, (2) strengthening inter-cultural and inter-generational dialogue and social integration, (3) developing essential social and personal skills, and (4) creating smooth spaces of democratic citizenship based on equality, collaboration, sharing, and caring. By understanding the tensions and conflicts that emerge in children's everyday situations, the project sought to build and foster community through embracing differences. This article analyzes the characteristics, behaviors, challenges, and strengths observed during the 30 sessions. The results provide insights into the dimensions of Children as commoners, in terms of sharing and care, cooperation and collective creativity and active citizenship. This research contributes to the exploration of Educational Commons as a means to promote equity and transform educational contexts.